Contemporary Compositional Techniques and Openmusic - Hirs, Rozalie; Gilmore, Bob 1961-2015 (Paris Delatour, 2009)
The first part of this book contains essay on musical works of Claude Vivier (Lonely Child, 1980), Gérard Grisey (Quatre chants pour franchir le seuil, 1997-1998) and Tristan Murail (Le Lac, 2001) by Bob Gilmore, Jean-Luc Hervé and Rozalie Hirs. The authors provide detailed analyses of these works, focusing on frequency-based techniques and compositional processes employed by the composers.The second part of the book originated in 'OpenMusic and Contemporary Compositional Techniques', a series of lectures and workshops by Rozalie Hirs and guest professors Tristan Murail, Mikhail Malt, Benjamin Thigpen, Marco Stroppa, and Niels Bogaards at the Conservatorium van Amsterdam during 2005/06 academic year. The series was initiated by the Nieuw Ensemble and its artistic director, Joël Bons, as part of the annual Componistenpracticum, which pairs theory and practice in a way not found anywhere else in the world. The Nieuw Ensemble and conductor Lucas Vis rehearsed and performed new pieces written by an international group of composition students from the Conservatorium van Amsterdam and the Royal Conservatoire in the Netherlands. In turn, the students documented their creative process in the seven essays included in this volume. An extensive essay on Tristan Murail's compositional ideas and frequency-based techniques originated in the lecture series given by Rozalie Hirs.It provides the most detailed discussion of Murail's work available in English today.The essays span a broad scope of compositional ideas involving, amongst others, frequency-based techniques, acoustic modeling, set theory and permutational techniques.
Keywords: Vivier, Claude -- 1948-1983; Grisey, Gérard -- 1946-1998; Murail, Tristan -- -1947; 20th Century (1901-2000); Musical analysis